Carbon Supported Gold Nanoparticles for the Catalytic Reduction of 4-Nitrophenol - Rodríguez Molina, Hugo; Santos Muñoz, José Luis; Domínguez Leal, María Isabel; Reina, Tomas Ramírez; Ivanova, Svetlana; Centeno Gallego, Miguel Ángel; Odriozola, José Antonio (Frontiers in Chemistry, 2019)
This work is a detailed study on how to optimize gold colloids preparation and their deposition to very different in nature carbon materials. The change of the continuous phase and its dielectric constant is used to assure the good dispersion of the hydrophilic/hydrophobic carbons and the successful transfer of the preformed small size colloids to their surface. The sintering behavior of the particles during the calcination step is also studied and the optimal conditions to reduce to a minimum the particle size increase during the protecting agent removal phase are found. The as prepared catalysts have been tested in a relevant reaction in the field of environmental catalysis such as the reduction of 4-nitrophenol leading to promising results. Overall, this work proposes an important methodology to follow when a carbonaceous material are selected as catalyst supports for green chemistry reactions.